2016
DOI: 10.1080/21690731.2016.1244031
|View full text |Cite
|
Sign up to set email alerts
|

RNA G-quadruplexes and their potential regulatory roles in translation

Abstract: DNA guanine (G)-rich 4-stranded helical nucleic acid structures called G-quadruplexes (G4), have been extensively studied during the last decades. However, emerging evidence reveals that 5′- and 3′-untranslated regions (5′- and 3′-UTRs) as well as open reading frames (ORFs) contain putative RNA G-quadruplexes. These stable secondary structures play key roles in telomere homeostasis and RNA metabolism including pre-mRNA splicing, polyadenylation, mRNA targeting and translation. Interestingly, multiple RNA bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 161 publications
(131 reference statements)
3
116
0
Order By: Relevance
“…The formation of RG4 structures — if validated inside cells — would represent the most stable RNA structure that could block ribosome scanning. Beyond the helicase eIF4A and in contrast to the extensively studied DNA G-quadruplexes 62 , other physiological roles of RG4s in mRNAs have only fairly recently been explored (reviewed in REFS 63,64) and include roles in mRNA processing and translation regulation (reviewed in REFS 65,66). Most examples of RG4s in 5′ UTRs are linked to translation repression in cis 65,67,68 presumably by preventing the 43S pre-initiation complex from binding to mRNA or by slowing down scanning 69,70 (FIG.…”
Section: ′ Utr Structures In Ribosome Scanningmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of RG4 structures — if validated inside cells — would represent the most stable RNA structure that could block ribosome scanning. Beyond the helicase eIF4A and in contrast to the extensively studied DNA G-quadruplexes 62 , other physiological roles of RG4s in mRNAs have only fairly recently been explored (reviewed in REFS 63,64) and include roles in mRNA processing and translation regulation (reviewed in REFS 65,66). Most examples of RG4s in 5′ UTRs are linked to translation repression in cis 65,67,68 presumably by preventing the 43S pre-initiation complex from binding to mRNA or by slowing down scanning 69,70 (FIG.…”
Section: ′ Utr Structures In Ribosome Scanningmentioning
confidence: 99%
“…Scanning inhibition is thought to be further increased by recruitment of RG4-stabilizing proteins 63,66 such as fragile X mental retardation protein (FMRP) 73 , which binds to many RG4-harbouring mRNAs 74,75 (FIG. 2b).…”
Section: ′ Utr Structures In Ribosome Scanningmentioning
confidence: 99%
“…The C9 repeats are notable for their ability to form highly stable G-quadruplex (G-Q) structures, which, interestingly, have been implicated in translational control (Bolduc et al 2016;Song et al 2016) and suggested to serve as internal ribosomal entry sites (Morris et al 2010). Expanded, long arrays of G-Q-forming sequences may give rise to complex mixtures of G-Q structures and linear G-tract RNA, which have been reported to bind RBPs such as hnRNP H (Conlon et al 2016), nucleolin (Haeusler et al 2014), and other known G-Q binders (Brazda et al 2014) as well as many other proteins ( Fig.…”
Section: Rna-centric Mechanisms In C9orf72 Als-ftdmentioning
confidence: 99%
“…Until recently, questions focused on the function of RNA G4 motifs in the 5´ UTR, which were shown to impact translation initiation and decrease protein expression by inhibiting the ribosome, using various reporter systems and in vivo approaches (Kumari et al, 2007; Song et al, 2016; Wolfe et al, 2014). G4 motifs in 3’ UTRs are less well studied but have been implicated in multiple processes including splicing, polyadenylation, and translation (Beaudoin and Perreault, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…G4 structures are stable DNA or RNA secondary structures that at their core contain stacked guanine tetrads built by Hoogsteen hydrogen bonding (Bochman et al, 2012; Millevoi et al, 2012; Rhodes and Lipps, 2015). The human genome is predicted to encode over 13,000 RNA-G4 structures (Kwok et al, 2016), which may impact a wide range of processes, including mRNA 3´end processing, or telomerase activity (Millevoi et al, 2012; Rhodes and Lipps, 2015; Song et al, 2016). Most intensively studied are the effects of RNA G4 structures on translation: they are postulated to influence cap-independent translation by altering IRES (Internal Ribosome Entry Site) recognition of viral and cellular transcripts (Baird et al, 2006; Bonnal et al, 2003; Cammas et al, 2015; Morris et al, 2010), or, depending on the location of the G4 structure, they block translational elongation (Endoh and Sugimoto, 2016; Thandapani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%